2021
DOI: 10.12659/msm.932361
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Diagnostic Model for Differentiating Between COVID-19 and Influenza: A 2-Center Retrospective Study

Abstract: Background COVID-19 and influenza share many similarities, such as mode of transmission and clinical symptoms. Failure to distinguish the 2 diseases may increase the risk of transmission. A fast and convenient differential diagnosis between COVID-19 and influenza has significant clinical value, especially for low- and middle-income countries with a shortage of nucleic acid detection kits. We aimed to establish a diagnostic model to differentiate COVID-19 and influenza based on clinical data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
(48 reference statements)
1
5
0
Order By: Relevance
“…Data from other studies have shown better diagnostic estimators for several of the clinical features that were included in this study, either in isolation or when integrated within multivariable models [ 21 , 22 , 23 ]. Estimators of precision well over 85% and ROC AUCs of 0.85–0.91 have been previously reported in the literature, findings that contrast with the more conservative AUC of roughly 0.75 that was found in both our simplified and full multivariable model [ 24 , 25 , 26 ]. It is likely that methodological differences explain these contrasts in accuracy, such as the retrospective nature of the aforementioned studies and the inclusion of non-clinical variables within models, such as computer tomography scans or laboratory data; in addition, the non-use of protective means may increase the predictive properties of the model.…”
Section: Discussionsupporting
confidence: 70%
“…Data from other studies have shown better diagnostic estimators for several of the clinical features that were included in this study, either in isolation or when integrated within multivariable models [ 21 , 22 , 23 ]. Estimators of precision well over 85% and ROC AUCs of 0.85–0.91 have been previously reported in the literature, findings that contrast with the more conservative AUC of roughly 0.75 that was found in both our simplified and full multivariable model [ 24 , 25 , 26 ]. It is likely that methodological differences explain these contrasts in accuracy, such as the retrospective nature of the aforementioned studies and the inclusion of non-clinical variables within models, such as computer tomography scans or laboratory data; in addition, the non-use of protective means may increase the predictive properties of the model.…”
Section: Discussionsupporting
confidence: 70%
“…Currently, the best-compared variance of mentioned parameters is between patients with COVID-19 and patients with influenza. Therefore, significantly higher CRP values on hospital admission were detected in influenza-positive subjects after comparing those groups of patients [ 44 ]. In their study, Kuang et al have evinced the higher incidence of influenza patients detected on admission with CRP value above 10 mg/dl and PCT value above 0.5 ng/mL, compared to COVID-19 patients [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 26 ] Therefore, developing an accurate diagnostic model that can effectively predict COVID-19 presence (diagnosis) with important prognostic determinants is indeed vital. [ 1 2 ] This study proposed an understandable, intuitive, and yet accurate prediction model using logistic regression based on the most important predictors.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that SARS-CoV-2 has animal origins that slipped from animal species into the human population. [ 1 2 ] The World Health Organization later on February 11, 2020 announced coronavirus disease 2019 “COVID-19” as the name of this new disease. [ 3 4 ] COVID-19 is a highly contagious viral infectious disease and continues to spreading aggressively around the whole world.…”
Section: Introductionmentioning
confidence: 99%